Highly heat-conductive polyimide film and method for manufacturing the same

CN116903898BActive Publication Date: 2026-11-03ANHUI GUOFENG PLASTIC +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310713423.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2026-11-03
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

Traditional polyimide films have low thermal conductivity, which limits their application in electrical equipment and smart grids. Hexagonal boron nitride alone is difficult to form an efficient thermal conduction path as a thermally conductive filler.

Method used

High thermal conductivity polyimide films were prepared by electrostatic self-assembly of positively charged g-C3N4 nanosheets and negatively charged boron nitride to form CNNns/BN hybrid thermally conductive fillers, which were then subjected to in-situ polymerization with diamine monomers and dianhydride monomers.

Benefits of technology

This improves the thermal conductivity and mechanical properties of the polyimide film, forms an efficient thermal conduction path, enhances compatibility with the polyimide matrix, reduces phonon scattering, and improves the thermal conductivity of the film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a high-thermal-conductivity polyimide film and a preparation method thereof. First, g-C3N4 nanosheets with positive charges on surfaces and boron nitride with negative charges on surfaces are combined into a CNNns / BN hybrid thermal-conductivity filler through electrostatic self-assembly. Then, the CNNns / BN hybrid thermal-conductivity filler and polyimide polymerization monomers are subjected to in-situ polymerization in a solvent to obtain a polyimide acid solution containing the CNNns / BN. Finally, defoaming, film casting and heat treatment are performed to obtain the polyimide film. The polyimide film prepared by the application has high thermal conductivity and good mechanical properties, and has good popularization and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyimide technology, and more particularly to a high thermal conductivity polyimide film and its preparation method. Background Technology

[0002] Polyimide (PI) is an aromatic heterocyclic polymer compound composed of imide-containing repeating units [-C(O)-N(R)-C(O)-]. It possesses excellent electrical insulation, radiation resistance, and mechanical properties, earning it the reputation of a "problem solver." PI has enormous development potential as a structural or functional material, especially PI film materials, often called "golden films." As one of the earliest developed and applied polyimide products, it is widely used in printed circuit boards, electronic packaging, interlayer dielectrics, and display panels. However, with technological advancements, electronic devices are becoming increasingly thinner, more multifunctional, and more integrated, inevitably leading to heat accumulation within composite materials, severely impacting the stable operation and lifespan of equipment. The traditional polyimide has a low intrinsic thermal conductivity (0.16 W / (m·K)), limiting its application in electrical equipment, smart grids, and other fields. Therefore, developing polyimide films with high thermal conductivity is essential. Hexagonal boron nitride, a two-dimensional material known as "white graphene," is chosen as a thermally conductive filler due to its excellent thermal conductivity. However, in practical applications, it is difficult to form an efficient thermal conduction path using only hexagonal boron nitride as a thermally conductive filler, and its effect on improving the thermal conductivity of polyimide films is limited. Summary of the Invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a high thermal conductivity polyimide film and its preparation method. The polyimide film prepared by the method has the advantages of high thermal conductivity and good mechanical properties, and the preparation process is simple.

[0004] The present invention discloses a method for preparing a high thermal conductivity polyimide film, comprising the following steps:

[0005] S1. In a solvent, positively charged g-C3N4 nanosheets and negatively charged boron nitride are electrostatically self-assembled to form CNNns / BN hybrid thermally conductive fillers.

[0006] S2. The CNNns / BN hybrid thermally conductive filler is subjected to in-situ polymerization with diamine monomer and dianhydride monomer in an organic solvent to obtain a polyamic acid solution containing CNNns / BN.

[0007] S3. The polyamic acid solution containing CNNns / BN is defoamed, cast into a film, and then subjected to segmented heating for desolventizing and thermal imidization to obtain the final product.

[0008] Preferably, in S1, g-C3N4 nanosheets prepared by acidification and exfoliation are electrostatically self-assembled with boron nitride with micro-oxidation on the surface in anhydrous ethanol to form CNNns / BN hybrid thermally conductive filler.

[0009] Preferably, in S1, the ethanol dispersion of g-C3N4 nanosheets prepared by acidification and exfoliation is mixed with the ethanol dispersion of boron nitride with micro-oxidation on the surface and then stirred to react, so that the g-C3N4 nanosheets are adsorbed onto the surface of boron nitride through electrostatic self-assembly to obtain CNNns / BN hybrid thermally conductive filler; preferably, the stirring reaction time is 1 to 3 hours.

[0010] In this invention, the preparation method of the g-C3N4 nanosheets prepared by acid exfoliation is a conventional method, which can be as follows: g-C3N4 is mixed with a strong acid, stirred for a period of time, then an appropriate amount of deionized water is added for ultrasonic exfoliation, followed by solid-liquid separation, and the obtained solid material is dried to obtain the product.

[0011] In this invention, g-C3N4 can be prepared by conventional methods, such as by high-temperature thermal polycondensation of melamine; preferably, the preparation method of g-C3N4 is as follows: melamine is placed in a crucible and calcined in a muffle furnace at 450-600°C for 2-4 hours, and then cooled to obtain the product.

[0012] In the preparation method of g-C3N4 nanosheets prepared by acid exfoliation, the stirring time is preferably 5-9 h, the ultrasonic exfoliation time is preferably 1-3 h, the strong acid is preferably hydrochloric acid with a concentration of 30-40%, the ratio of g-C3N4 to strong acid is preferably 1 g: 15-20 mL, and the volume ratio of strong acid to deionized water is preferably 1: (1-2).

[0013] Preferably, the surface-micro-oxidized boron nitride is obtained by calcining boron nitride at high temperature in an air atmosphere or an oxygen atmosphere; preferably, the conditions for high-temperature calcination are: calcination at 700-1000℃ for 1-3 hours.

[0014] Preferably, the method for preparing the surface-micro-oxidized boron nitride is as follows: in an air atmosphere, boron nitride is placed in a crucible and calcined in a muffle furnace at 700-1000°C for 1-3 hours, and then cooled to obtain the product.

[0015] Preferably, the boron nitride is hexagonal spherical boron nitride; preferably, the particle size of the boron nitride is 10-25 μm.

[0016] Preferably, the mass ratio of the g-C3N4 nanosheets to boron nitride is 0.2 to 1:1.

[0017] Preferably, in step S2, the CNNns / BN hybrid thermally conductive filler is dispersed in an organic solvent, then a diamine monomer is added and stirred for a period of time, followed by the addition of a dianhydride monomer and stirring to obtain a polyamic acid solution containing CNNns / BN; preferably, the mass ratio of the CNNns / BN hybrid thermally conductive filler to the diamine monomer is 0.2–1.5:1; preferably, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1–1.05; preferably, the diamine monomer is added and stirred for 1–2 hours; preferably, the dianhydride monomer is added and stirred until the viscosity reaches 50,000–150,000 mPa·s.

[0018] Preferably, in S3, the specific steps for desolventizing and thermal imidization by segmented heating are as follows: first, desolventizing at 100-120°C for 30-50 min, then sequentially holding at 140-180°C for 30-45 min, holding at 190-230°C for 30-45 min, holding at 240-280°C for 30-45 min, and holding at 290-320°C for 30-45 min.

[0019] Preferably, in S2, the diamine monomer is one or two of p-phenylenediamine, m-phenylenediamine, biphenylenediamine, and 4,4′-diaminodiphenyl ether; the dianhydride monomer is one of pyromellitic dianhydride and 3,3′,4,4′-biphenyltetracarboxylic dianhydride; and the organic solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0020] A high thermal conductivity polyimide film is prepared by the method described above.

[0021] The beneficial effects of this invention are as follows:

[0022] This invention first involves electrostatically self-assembling positively charged g-C3N4 nanosheets (CNNns) and negatively charged boron nitride (BN) in a solvent to form a CNNns / BN hybrid thermally conductive filler. This filler is then in-situ polymerized with diamine and dianhydride monomers of polyimide in an organic solvent to obtain a polyamic acid solution containing CNNns / BN. Finally, after defoaming and casting, the solution is desolventized and thermally imidized in stages to obtain a polyimide film. In the CNNns / BN hybrid thermally conductive filler of this invention, CNNns adsorbed on the BN surface can synergistically promote the formation of a three-dimensional thermally conductive network, thereby constructing an efficient thermally conductive pathway and improving the thermal conductivity of PI. Furthermore, the strong interaction between the -NH2 on the CNNns surface and the -COOH of the polyamic acid effectively promotes the compatibility of the CNNns / BN hybrid thermally conductive filler with the PI matrix, thereby suppressing interfacial interactions and reducing phonon scattering at the interface in the PI matrix, further improving the thermal conductivity of PI. The polyimide film prepared by this invention has high thermal conductivity and good mechanical properties, and has great potential for widespread application. Detailed Implementation

[0023] The technical solution of the present invention will now be described in detail through specific embodiments.

[0024] Example 1

[0025] Preparation of g-C3N4:

[0026] 5g of melamine was placed in a crucible, which was then placed in a muffle furnace and kept at 450℃~600℃ for 3h to obtain g-C3N4.

[0027] Preparation of g-C3N4 nanosheets by acid exfoliation:

[0028] Take 2g g-C3N4 and 30ml of 36% hydrochloric acid and mix them evenly in a beaker. Stir with a magnetic stirrer for 6h, then add 30ml of deionized water and sonicate for 2h. Then centrifuge and dry to obtain CNNns.

[0029] Preparation of boron nitride with micro-oxidation on the surface:

[0030] Weigh 5g of boron nitride, place it in a muffle furnace, and calcine it at 900℃ for 2h in air atmosphere to perform surface micro-oxidation. After cooling, the boron nitride is obtained. The boron nitride is hexagonal spherical boron nitride with a particle size of 10-25μm.

[0031] Preparation of high thermal conductivity polyimide films:

[0032] S1. 2g of surface-micro-oxidized boron nitride was dispersed in 60ml of anhydrous ethanol to obtain an ethanol dispersion of surface-micro-oxidized boron nitride; 1g of CNNns was dispersed in 30ml of anhydrous ethanol to obtain an ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation; the ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation was mixed with the ethanol dispersion of surface-micro-oxidized boron nitride and stirred for 2h. After the reaction was completed, the mixture was centrifuged and dried to obtain CNNns / BN hybrid thermally conductive filler.

[0033] S2. Add 2.7g CNNns / BN hybrid thermally conductive filler to 128ml DMAC and sonicate for 1h. Then add 3g PDA (p-phenylenediamine) and 7g ODA (4,4'-diaminodiphenyl ether) and stir for 2h. Then add 13.69g PMDA to the above solution (pyromellitic dianhydride) in three portions and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing CNNns / BN.

[0034] S3. The polyamic acid solution containing CNNs / BN is subjected to vacuum defoaming treatment at -1 MPa. Then, it is coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. The film is then desolventized at 100℃ for 40 min, and then thermally imidized by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a high thermal conductivity polyimide film is obtained.

[0035] Example 2

[0036] The method for preparing g-C3N4 nanosheets with micro-oxidized boron nitride and acid exfoliation is the same as in Example 1.

[0037] Preparation of high thermal conductivity polyimide films:

[0038] S1. 5g of surface-micro-oxidized boron nitride was dispersed in 150ml of anhydrous ethanol to obtain an ethanol dispersion of surface-micro-oxidized boron nitride; 2.5g of CNNns was dispersed in 75ml of anhydrous ethanol to obtain an ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation; the ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation and the ethanol dispersion of surface-micro-oxidized boron nitride were mixed and stirred for 2h. After the reaction was completed, the mixture was centrifuged and dried to obtain CNNns / BN hybrid thermally conductive filler.

[0039] S2. Add 6g of CNNns / BN hybrid thermally conductive filler to 144ml of DMAC and ultrasonically disperse for 1h. Then add 3g of PDA and 7g of ODA and stir for 2h. Then add 13.69g of PMDA in three portions to the above solution and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing CNNns / BN.

[0040] S3. The polyamic acid solution containing CNNs / BN is subjected to vacuum defoaming treatment at -1 MPa. Then, it is coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. The film is then desolventized at 100℃ for 40 min, and then thermally imidized by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a high thermal conductivity polyimide film is obtained.

[0041] Example 3

[0042] The method for preparing g-C3N4 nanosheets with micro-oxidized boron nitride and acid exfoliation is the same as in Example 1.

[0043] Preparation of high thermal conductivity polyimide films:

[0044] S1. 8g of surface-micro-oxidized boron nitride was dispersed in 240ml of anhydrous ethanol to obtain an ethanol dispersion of surface-micro-oxidized boron nitride; 4g of CNNns was dispersed in 120ml of anhydrous ethanol to obtain an ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation; the ethanol dispersion of g-C3N4 nanosheets prepared by acid exfoliation and the ethanol dispersion of surface-micro-oxidized boron nitride were mixed and stirred for 2h. After the reaction was completed, the mixture was centrifuged and dried to obtain CNNns / BN hybrid thermally conductive filler.

[0045] S2. Add 10.2g CNNns / BN hybrid thermally conductive filler to 165ml DMAC and ultrasonically disperse for 1h. Then add 3g PDA and 7g ODA and stir for 2h. Then add 13.69g PMDA in three portions to the above solution and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing CNNns / BN.

[0046] S3. The polyamic acid solution containing CNNs / BN is subjected to vacuum defoaming treatment at -1 MPa. Then, it is coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. The film is then desolventized at 100℃ for 40 min, and then thermally imidized by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a high thermal conductivity polyimide film is obtained.

[0047] Comparative Example 1

[0048] Preparation of polyimide films:

[0049] S1. Add 2.7g of boron nitride to 128ml of DMAC and sonicate for 1h. Then add 3g of PDA and 7g of ODA and stir for 2h. Then add 13.69g of PMDA to the above solution in three portions and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing BN, wherein the boron nitride is hexagonal spherical boron nitride with a particle size of 10-25μm.

[0050] S3. The polyamic acid solution containing BN is subjected to vacuum defoaming treatment under -1 MPa conditions, and then coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. Then, the solvent is removed at 100℃ for 40 min, and then thermal imidization is performed by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a polyimide film is obtained.

[0051] Comparative Example 2

[0052] Preparation of polyimide films:

[0053] S1. Add 6g of boron nitride to 144ml of DMAC and sonicate for 1h. Then add 3g of PDA and 7g of ODA and stir for 2h. Then add 13.69g of PMDA to the above solution in three portions and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing BN, wherein the boron nitride is hexagonal spherical boron nitride with a particle size of 10-25μm.

[0054] S3. The polyamic acid solution containing BN is subjected to vacuum defoaming treatment under -1 MPa conditions, and then coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. Then, the solvent is removed at 100℃ for 40 min, and then thermal imidization is performed by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a polyimide film is obtained.

[0055] Comparative Example 3

[0056] Preparation of polyimide films:

[0057] S1. Add 10.2g of boron nitride to 165ml of DMAC and sonicate for 1h. Then add 3g of PDA and 7g of ODA and stir for 2h. Then add 13.69g of PMDA to the above solution in three portions and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing BN, wherein the boron nitride is hexagonal spherical boron nitride with a particle size of 10-25μm.

[0058] S3. The polyamic acid solution containing BN is subjected to vacuum defoaming treatment under -1 MPa conditions, and then coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. Then, the solvent is removed at 100℃ for 40 min, and then thermal imidization is performed by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a polyimide film is obtained.

[0059] Comparative Example 4

[0060] Preparation of polyimide films:

[0061] S1. Add 1.8g boron nitride and 0.9g g-C3N4 nanosheets to 128ml DMAC and disperse ultrasonically for 1h. Then add 3g PDA and 7g ODA and stir for 2h. Then add 13.69g PMDA in three portions to the above solution and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution containing BN and g-C3N4. The boron nitride is hexagonal spherical boron nitride with a particle size of 10-25μm. The preparation method of g-C3N4 nanosheets is the same as in Example 1.

[0062] S3. The polyamic acid solution containing BN and g-C3N4 is subjected to vacuum defoaming treatment at -1 MPa. Then, it is coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. The film is then desolvated at 100℃ for 40 min, and then thermal imidized by holding at 160℃ for 35 min, 210℃ for 35 min, 260℃ for 35 min, and 310℃ for 35 min in sequence. After cooling, a polyimide film is obtained.

[0063] Comparative Example 5

[0064] Preparation of polyimide films:

[0065] S1. Add 3g PDA and 7g ODA to 115mL DMAC and stir for 2h. Then add 13.69g PMDA to the above solution in three portions and stir until the viscosity is 80000mPa·s to obtain a polyamic acid solution.

[0066] S3. The polyamic acid solution is defoamed under vacuum at -1 MPa, and then coated onto a glass plate using an automatic coating machine to form a film with a thickness of 50 μm. The film is then desolventized at 100°C for 40 min, and then thermally imidized at 160°C for 35 min, 210°C for 35 min, 260°C for 35 min, and 310°C for 35 min in sequence. After cooling, a polyimide film is obtained.

[0067] Test case

[0068] The thermal conductivity and mechanical properties of the polyimide films prepared in Examples 1-3 and Comparative Examples 1-5 were tested, and the results are shown in Table 1.

[0069] Among them: thermal conductivity test: tested according to Hot Disk ISO 22007-2 standard; mechanical property test: tested according to GB / T 1040.3-2006 standard.

[0070] Table 1. Thermal conductivity and mechanical properties of polyimide films.

[0071] Serial Number Thermal conductivity (W / (m·K)) Tensile strength (MPa) Example 1 0.41 131.8 Example 2 0.62 122.3 Example 3 0.87 111.7 Comparative Example 1 0.32 123.2 Comparative Example 2 0.43 109.5 Comparative Example 3 0.56 93.4 Comparative Example 4 0.35 120.1 Comparative Example 5 0.18 145.2

[0072] As shown in Table 1, compared to Comparative Example 5 without any thermally conductive filler, the thermal conductivity of the films in Examples 1-3 and Comparative Examples 1-4 is improved. However, compared to Comparative Examples 1-4, Examples 1-3 have better thermal conductivity with the same amount of thermally conductive filler. This may be because CNNs adsorbed on the BN surface exert a synergistic effect to form an efficient thermal conduction pathway and improve its compatibility with polyimide, thereby enhancing its thermal conductivity. In addition, compared to Comparative Example 5, the tensile strength in Examples 1-3 of this invention decreases less, ensuring the normal use of the polyimide film.

[0073] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a high thermal conductivity polyimide film, characterized in that, Includes the following steps: S1. An ethanol dispersion of g-C3N4 nanosheets prepared by acidification and exfoliation is mixed with an ethanol dispersion of boron nitride with micro-oxidation on the surface, and then stirred to react. This allows the g-C3N4 nanosheets to be adsorbed onto the surface of boron nitride through electrostatic self-assembly, resulting in a CNNns / BN hybrid thermally conductive filler. The boron nitride is hexagonal spherical with a particle size of 10~25μm. The mass ratio of g-C3N4 nanosheets to boron nitride is 0.2~1:

1. S2. The CNNns / BN hybrid thermally conductive filler is subjected to in-situ polymerization with diamine monomer and dianhydride monomer in an organic solvent to obtain a polyamic acid solution containing CNNns / BN. S3. The polyamic acid solution containing CNNns / BN is defoamed, cast into a film, and then subjected to segmented heating for desolventizing and thermal imidization to obtain the final product.

2. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, In S1, the stirring reaction takes 1 to 3 hours.

3. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, The preparation method of the g-C3N4 nanosheets prepared by acid exfoliation is as follows: g-C3N4 is mixed with a strong acid, stirred for a period of time, then an appropriate amount of deionized water is added for ultrasonic exfoliation, followed by solid-liquid separation, and the obtained solid material is dried to obtain the nanosheets.

4. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, The surface-micro-oxidized boron nitride is obtained by calcining boron nitride at high temperature in an air or oxygen atmosphere.

5. The method for preparing a high thermal conductivity polyimide film according to claim 4, characterized in that, The conditions for high-temperature calcination are: calcination at 700~1000℃ for 1~3 hours.

6. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, In S2, the diamine monomer is dissolved in an organic solvent, then a dispersion of CNNns / BN hybrid thermally conductive filler is added and stirred to react, followed by the addition of dianhydride monomer and stirring to react, resulting in a polyamic acid solution containing CNNns / BN.

7. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, The mass ratio of the CNNns / BN hybrid thermally conductive filler to the diamine monomer is 0.2~1.5:

1.

8. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, The molar ratio of the diamine monomer to the dianhydride monomer is 1:1 to 1.

05.

9. The method for preparing a high thermal conductivity polyimide film according to claim 6, characterized in that, The dispersion of CNNns / BN hybrid thermally conductive filler was added and stirred for 1-2 hours.

10. The method for preparing a high thermal conductivity polyimide film according to claim 6, characterized in that, Add dianhydride monomer and stir to react until the viscosity reaches 50,000~150,000 mPa·s.

11. The method for preparing a high thermal conductivity polyimide film according to claim 1, characterized in that, In S3, the specific steps for desolventizing and thermal imidization by segmented heating are as follows: first, desolventize at 100~120℃ for 30~50 min, then hold at 140~180℃ for 30~45 min, hold at 190~230℃ for 30~45 min, hold at 240~280℃ for 30~45 min, and hold at 290~320℃ for 30~45 min.

12. A high thermal conductivity polyimide film, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • High-thermal-conductivity polyimide film and application thereof

    CN115558292A